(untitled) (Current Horticulture, 2024)
Elephantfoot yam and taro are important aroids of tropical tuber crops and considered as underutilized in the context of climate change and food security. This study focuses on the existing modelling studies on growth, yield, and future climate suitability of elephantfoot yam and taro. Among different crop models, SUBSTOR-Aroids, AquaCrop, and WOFOST are tested internationally to simulate the crop growth and yield of aroids. The QUEFTS model is tested in India for aroids in estimating crop yield based on site-specific nutrient management. EcoCrop is used to predict the future climate suitability of aroids. This review indicates very limited studies are available for aroids compared to other tropical tuber crops. This shows the necessity to focus more on these underutilized aroids as they are superior in per hectare production to that of major foodgrain crops. This review also recommends modelling studies on aroids to identify or develop a better model structure irrespective of the agro climatic conditions.